Mercury fractionation in dourada (Brachyplatystoma rousseauxii) of the Madeira River in Brazil using metalloproteomic strategies - Braga, C. P. [UNESP]; Bittarello, A. C. [UNESP]; Padilha, C. C. F. [UNESP]; Leite, A. L.; Moraes, P. M. [UNESP]; Buzalaf, M. A. R.; Zara, L. F.; Padilha, P. M. [UNESP] (Elsevier B.V., 2015)
This paper presents the results of mercury fractionation in muscle samples of dourada (Brachyplatystoma rousseauxii) from the JIRAU Hydroelectric Power Plant in the Madeira River Basin in the Amazon region of Brazil. The proteome of the dourada muscle was separated by two-dimensional polyacrylamide gel electrophoresis (2D PAGE). The mercury present in the protein spots was determined by graphite furnace atomic absorption spectrometry (GFAAS) after acid mineralisation in an ultrasound bath. The protein spots in which the presence of mercury was detected were characterised by electrospray ionisation tandem mass spectrometry (ESI-MS/MS) after tryptic digestion. The GFAAS determinations indicated that 65% of the mercury was linked to the protein fraction with a molar mass (Mm) of less than 90 kDa. The mercury concentrations in the seven spots in which this protein fraction was present were in the range of 11.40-35.10 mu g kg(-1). Based on the mercury concentrations, it was possible to estimate that the protein spots contained approximately 1-3 mercury atoms per protein molecule. The ESI-MS/MS analysis allowed characterisation of the seven protein spots as the following proteins: protein NLRC5 (molar mass=18.10, pI=6.30); 39S ribosomal protein L36 mitochondrial (molar mass=15.40, pI=8.23); N-alpha-acetyltransferase 20 (Mm=15.95, pI=8.80); Mth938 domain-containing protein (Mm=15.01, pI=9.60); ubiquitin-40S ribosomal protein S27a (Mm=9.80, pI=7.60); parvalbumin alpha (Mm=12.40, pI=3.80) and parvalbumin beta (Mm=13.10, pI=3.45).
Keywords: Mercury in amazon fish; Metallomics; 2D PAGE; GFAAS; ESI-MS/MS